The Influence of Attitudes, Perception of Control and Internal Control System on Whistleblowing Intention with Legal Protection as a Moderation Variable (study on PT Kereta API Indonesia) - Primasari, Dona; Waspodo, Lego; Ilhami, Muhammad Thareq (Buhalterinės apskaitos teorija ir praktika, 2022)
This study aims to determine, analyze, and test the effect of attitudes, perceptions of control, and internal control systems on whistleblowing intentions with legal protection as a moderating variable. This type of research is survey research with a quantitative approach. The population in this study were employees who worked at PT Kereta Api Indonesia Daop 5 Purwokerto. The sample selection used purposive sampling method. The results of this study indicate that: 1) Attitude has a significant effect on the intention to take whistleblowing action. 2) Perceived control has no effect on the intention to take whistleblowing action on employees PT Kereta Api Indonesia Daop 5. 3) The internal control system has no effect on the intention to take whistleblowing action. 4) Legal protection cannot moderate the effect of attitudes on intentions to take whistleblowing actions. 5) Legal protection cannot moderate the influence of perceptions of control on the intention to take whistleblowing actions. 6) Legal protection cannot moderate the influence of the internal control system on the intention to take whistleblowing action.